FIRAT ÜNİVERSİTESİ BEDEN EĞİTİMİ VE SPOR YÜKSEK OKULU BÖLÜMLERİNDE OKUYAN ÖĞRENCİLERİN ÇOKLU ZEKÂ KURAMINA GÖRE KARŞILAŞTIRILMASI - KAYA, NURGÜL (Fırat Üniveristesi, 2012)
Yapılan çalışmada Fırat Üniversitesi Beden Eğitimi ve Spor Yüksekokulunun 3 bölümünde okuyan öğrencilerin çoklu zeka kuramına göre karşılaştırılması amaç edinilmiştir. Fırat Üniversitesi 1. Sınıf öğrencilerine uygulanan bu çalışma ile bölümler arasındaki farklılıklar test edilmeye çalışılmıştır.Araştırmanın çalışma evrenini Elazığ ili Fırat Üniversitesi Beden Eğitimi ve Spor Yüksekokulu öğrencileri, örneklemini ise Öğretmenlik, Antrenörlük gece-gündüz ve Spor Yöneticiliği gece-gündüz Bölümleri 1. Sınıf öğrencileri oluşturmaktadır. Toplam 214 kız - erkek gönüllü öğrenci katılmıştır. Araştırmada Howard Gardner tarafından geliştirilen geçerlilik ve güvenilirliği yapılmış olan "Çoklu Zeka Alanlarında Kendini Değerlendirme Envanteri" uygulanmıştır. 5'li Likert tipine göre derecelendirilmiştir. Envanter 80 sorudan oluşmaktadır. 8 zeka kuramı ve her zeka kuramından 10 soru mevcuttur. Sorular karışık olarak düzenlenmiştir. Envanter aynı hafta içerisinde öğrencilere uygulanmıştır.Üniversiteli öğrenciler için anket formu kullanılmıştır. Üniversite öğrencilerinin görüşleri cinsiyet farklarına ve hem kendi bölümleri içinde, hem de diğer bölümlerle karşılaştırılmıştır. p<0,05 anlamlılık düzeyi olarak kabul edilmiştir. Araştırmada, verilerin analizi bilgisayar ortamında SPSS 15.0 programı kullanılarak gerçekleştirilmiştir.

School of Physical Education and Sports sections of the multiple intelligence theory, according to the comparison students were targeted. Students in different parts of the multiple intelligence theory to show differences in terms of the phenomenon is the basis of research. Fırat University 1 Class includes students as a result of this work.Elazığ province of the operation of the survey universe of Physical Education and Sports, Fırat University Physical Education and Sports sections students, the Teacher of the sample, Coaching and Sport sections of the night and day, Management Department sections of the night and day 1st Class consists of students. Total of 214 students of the teacher section, the coaching section and the sports management of the students. Research developed by Howard Gardner and Gonce Turkish by Seber validity and reliability that has "Multiple Intelligence Self-Assessment Inventory in the Area" has been applied. Inventory consists of 80 questions. Intelligence theory and intelligence theory 8 is available from the 10 questions. Questions will be mixed.The scope of this research, college students, I used the survey form. Demographic characteristics of university students according to the views of relationships have been cross-checked with tables and p = 0.05 level of significance was considered to be. Research, the analysis by using computer programs are conducted in SPSS 15.0.KEY WORD: Multiple Intelligence Self-Assessment Inventory in the Area, Physical Education and Sport, Training, Management,
The comparison of the according to the theory of multiple intelligences of students in departments of physical education and sport
Keywords: Spor